Stimulation of Single, Possible CHX10 Hindbrain Neurons Turns Swimming On and Off in Young Xenopus Tadpoles - Li, Wen-Chang; Soffe, Stephen R. (Frontiers in Cellular Neuroscience, 2019)
Vertebrate central pattern generators controlling locomotion contain neurons which provide the excitation that drives and maintains network rhythms. In a simple vertebrate, the developing Xenopus tadpole, we study the role of excitatory descending neurons with ipsilateral projecting axons (dINs) in the control of swimming rhythms. In tadpoles with both intact central nervous system and transections in the hindbrain, exciting some individual dINs in the caudal hindbrain region could start swimming repeatedly. Analyses indicated the recruitment of additional dINs immediately after such evoked dIN spiking and prior to swimming. Excitation of dINs can therefore be sufficient for the initiation of swimming. These ‘powerful’ dINs all possessed both ascending and descending axons. However, their axon projection lengths were not different from those of other excitatory dINs at similar locations. The dorsoventral position of dINs, as a population, significantly better matched that of cells marked by immunocytochemistry for the transcription factor CHX10 than other known neuron types in the ventral hindbrain and spinal cord. The comparison suggests that the excitatory interneurons including dINs are CHX10-positive, in agreement with CHX10 as a marker for excitatory neurons with ipsilateral projections in the spinal cord and brainstem of other vertebrates. Overall, our results further demonstrate the key importance of dINs in driving tadpole swimming rhythms.